Impact of spherical applicator diameter on relative biologic effectiveness of low energy IORT X-rays: A hybrid Monte Carlo study. (December 2020) - Shamsabadi, Reza; Baghani, Hamid Reza; Azadegan, Behnam; Mowlavi, Ali Asghar
Highlights: RBE values for low-kV IORT X-rays were evaluated by a hybrid simulation approach. Presence of spherical applicators substantially changes the bare probe RBE value. Variations of spherical applicator diameters have less impact on RBE value. The RBE of low-kV IORT X-rays is about 40% higher than MV photon beam. Abstract: Introduction: Low-kV IORT (Low kilovoltage intraoperative radiotherapy) using INTRABEAM machine and dedicated spherical applicators is a candidate modality for breast cancer treatment. The current study aims to quantify the RBE (relative biologic effectiveness) variations of emitted X-rays from the surface of different spherical applicators and bare probe through a hybrid Monte Carlo (MC) simulation approach. Materials and methods: A validated MC model of INTRABEAM machine and different applicator diameters, based on GEANT4 Toolkit, was employed for RBE evaluation. To doing so, scored X-ray energy spectra at the surface of each applicator diameter/bare probe were used to calculate the corresponding secondary electron energy spectra at various distances inside the water and breast tissue. Then, MCDS (Monte Carlo damage simulation) code was used to calculate the RBE values according to the calculated electron spectra. Results: Presence of spherical applicators can increase the RBE of emitted X-rays from the bare probe by about 22.3%. In return, changing the applicator diameter has a minimal impact (about 3.2%) on RBE variation of emitted X-rays from each applicator surface. By increasing the distance from applicator surface, the RBE increments too, so that its value enhances by about 10% with moving from 2 to 10 mm distance. Calculated RBE values within the breast tissue were higher than those of water by about 4% maximum value. Conclusion: Ball section of spherical IORT applicators can affect the RBE value of the emitted X-rays from INTRABEAM machine. Increased RBE of breast tissue can reduce the prescribed dose for breast irradiation if INTRABEAM machine has been calibrated inside the water.